Development of the College Management Model with a Core Concept towards Sustainability for the College of Office of the Vocational Education Commission - Kaenthip Kawiset, Charuwan; Chianchana, Chaiwichit; Na Wichian, Sageemas (Ratchaphruek Journal, 2024)
The objectives of this research were: 1) To develop a college management model with the core concept towards sustainability for the college of Office of the Vocational Education Commission; 2) To assess the propriety and feasibility of the management model with the core concept towards sustainability; and 3) To evaluate the model for accuracy, utility, and evaluation accountability standard. The main data providers consist of 9 qualified personnel confirming the vision and 11 expert evaluators recruited through purposive sampling. The research tools include content analysis questionnaires, group interview recording forms, propriety and feasibility assessment forms, accuracy, utility, and evaluation accountability standard. assessment forms, and analysis of data using content analysis and basic statistics such as mean and standard deviation. The research findings were: 1) A college management model with the core concept towards sustainability consisted of three main dimensions: human resource management, organizational design and processes, and student and stakeholder engagement. 2) The results of constructing a college management model, revealed high level of experts’ consensus on propriety and maximum feasibility for implementation. 3) The evaluation of a college management model by 11 expert college administrators shows a consensus that it is accurate, utility, and evaluation accountability highly level.